Sistem Aktivitas Harian Pegawai Berbasis Web - Sri Devi, Ni Komang; Bayu Atmaja Darmawan, I Dewa Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2019)
Human Resources Development and Human Resources Agency or abbreviated as BKPSDM Gianyar Regency is a government agency that has the main function of serving personnel administration in the Gianyar Regency Government environment. In daily activities the employees are obliged to make a daily work report, but the process is still manual by using office excel which takes a long time. A system is needed to handle this to make it easier for employees to make and print their daily work reports. This system is built using HTML, PHP, CSS and PHPMyAdmin for MySQL database management. System testing with black box method is intended to test the suitability of the software elements that are made. Keywords: System, Database, HTML, PHP, Black box.